Nano [compact disc, unabridged] - Cook, Robin 1940- (Penguin Audio, 2012)
Pia takes a year off from her medical studies to work at Nanobots, a lavish nanotechnology institute that is a leader in the construction of microbivores, tiny nano-robots than can gobble up viruses and bacteria. But troubling occurrences cause her to wonder: is the tech giant on the cusp of huge medical discoveries, or have they already sold out to the highest bidder?